1999
DOI: 10.1029/98ja02817
|View full text |Cite
|
Sign up to set email alerts
|

Global O/N2 derived from DE 1 FUV dayglow data: Technique and examples from two storm periods

Abstract: It is now well established that high-latitude forcing (heating and convection) can lead to significant thermospheric disturbances on a global scale. The basic scenario is upwelling of air from the lower thermosphere within the auroral oval due to Joule/particle heating followed by horizontal advection of this molecular rich air through a combination of diurnal tidal motion and ion convection effects. During storms, a strong increase in ion convection can produce a wind surge (due to ion/neutral coupling) out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…Changes in O/N 2 in these regions have been the subject of much study since 1956, when Seaton (1956) first showed that temperature changes were insufficient to explain the observed depletions of electron densities during geomagnetic storms and suggested that predominant process driving these depletions might be an enhancement of O 2 instead. Over the years comprehensive experimental studies, particularly by Pro¨lss (e.g., see Pro¨lss, 1980 for a list of the early experimental studies; also see Strickland et al, 1999 for more modern techniques that have been applied to this problem), and related theoretical work (e.g., Hays et al, 1973;Fuller-Rowell et al, 1991, 1996Burns et al, 1991) have lead both to a good description of the behavior of this enhanced N 2 and O 2 and a reasonable explanation of why they occur. The classical picture of the disturbance given by Pro¨lss (1981) involves the extension of the disturbance equatorward of the auroral oval after midnight through to the period after dawn.…”
Section: Article In Pressmentioning
confidence: 98%
“…Changes in O/N 2 in these regions have been the subject of much study since 1956, when Seaton (1956) first showed that temperature changes were insufficient to explain the observed depletions of electron densities during geomagnetic storms and suggested that predominant process driving these depletions might be an enhancement of O 2 instead. Over the years comprehensive experimental studies, particularly by Pro¨lss (e.g., see Pro¨lss, 1980 for a list of the early experimental studies; also see Strickland et al, 1999 for more modern techniques that have been applied to this problem), and related theoretical work (e.g., Hays et al, 1973;Fuller-Rowell et al, 1991, 1996Burns et al, 1991) have lead both to a good description of the behavior of this enhanced N 2 and O 2 and a reasonable explanation of why they occur. The classical picture of the disturbance given by Pro¨lss (1981) involves the extension of the disturbance equatorward of the auroral oval after midnight through to the period after dawn.…”
Section: Article In Pressmentioning
confidence: 98%
“…Such an approach has the disadvantage to analyze brightnesses acquired by two kinds of instruments and dominated by emissions produced by different atmospheric components. The derivation of the electron mean energy is strongly dependent on the N 2 to O ratio, which is very sensitive to the magnetospheric activity [e.g., Strickland et al , 1999; Drob et al , 1999]. In addition, the retrieval of the energy flux is very sensitive to the electron mean energy, as the WIC spectral range covers part of the N 2 LBH emissions which is strongly affected by O 2 absorption.…”
Section: Retrieving the Electron Mean Energy And Energy Flux From Fuvmentioning
confidence: 99%
“…Global satellite measurements have confirmed that particle and Joule heating during geomagnetic substorms can produce significant upwelling of air from the lower thermosphere, leading to depletions in the column density of atomic oxygen over large geographical regions outside auroral regions. These have been seen by the DE-1 FUV imager (e.g., Craven et al (1994), Nicholas et al (1997), Immel et al (1997), Strickland et al (1999), and Drob et al (1999)). …”
Section: Introductionmentioning
confidence: 97%